The Content of Non Verbal Communication Values in the Book Sulam Al-Munawwaraq Fil ‘Ilmi Mantiq - Halimatussa’diah Halimatussa’diah (Budapest International Research and Critics University, 2020)
Non-verbal communication is often used to describe feelings, emotions, and others. Non-verbal communication can strengthen and complement verbal communication. Therefore, in life must combine the two communications. Like the nazham contained in the al-Munawwaraq embroidery Fil ‘Ilmi Mantiq. Which explains about lafadh and ghairu lafadh both are related to one another. So that both the majority of students and some teachers who study the book sulam al-Munawwaraq Fil ‘Ilmi Mantiq do not know that there is a discussion of communication in the nazham. The phenomenon finally motivated a study entitled